Economic valuation of Kampung Rawa tourism development by CVM approach in Bejalen Village, Semarang Regency - Laily Nur Aini; Arfin Haryono; Dea Anas Stasya Insani (Indonesian Journal of Islamic Economics Research, 2022)
One of the tourist attractions in Semarang Regency is Kampung Rawa in Bejalen Village, Semarang Regency. The existence of Kampung Rawa becomes an instrument of local economic development in Bejalen Village. So, Kampung Rawa needs to be developed by making a selfie spot in Kampung Rawa interesting to visitors. This study aims to develop a hypothetical market development of selfie tourist attractions. The method in this study is a survey method for calculating economic value using contingent valuation methods (CVM). The results of this research are visitors are willing to pay (WTP) for the development of Kampung Rawa tourism. The average value of the WTP can be used as a reference for determining entry tickets for visitors allocated to develop Kampung Rawa tourism in Bejalen Village.